An experimental investigation on cutting-induced damage when drilling high-strength T800S/250F carbon fiber–reinforced polymer. (September 2017) - Xu, Jinyang; An, Qinglong; Chen, Ming
In modern manufacturing sectors, mechanical drilling of high-strength carbon fiber–reinforced polymer represents the most challenging task as compared to conventional low-strength carbon fiber–reinforced polymer drilling due to the extremely superior mechanical/physical properties involved. The poor machinability of the composite usually results in serious geometric imperfection and physical damage in drilling and hence leads to a large amount of part rejections. In this article, an experimental investigation concerning the cutting-induced damage when drilling high-strength carbon fiber–reinforced polymer laminates was presented. The studied composite specimen was a newly developed high-strength T800S/250F carbon fiber–reinforced polymer composite. A special concentration was made to inspect and characterize the phenomena of various cutting-induced damage promoted in the material drilling. The work focused on the study of the influence of cutting parameters on the distribution and extent of hole damage formation. The experimental results highlighted the most influential factor of feed rate and tool wear in affecting the final extent of induced hole damage when drilling high-strength T800S/250F carbon fiber–reinforced polymer. For minimizing the various damage formation, optimal cutting parameters (high spindle speed and low feed rate) and rigorous control of tool wear should be seriously taken when drilling this material.